Vesicle capture by membrane‐bound Munc13‐1 requires self‐assembly into discrete clusters. Issue 17 (24th July 2021) - Li, Feng; Kalyana Sundaram, Ramalingam Venkat; Gatta, Alberto T.; Coleman, Jeff; Ramakrishnan, Sathish; Krishnakumar, Shyam S.; Pincet, Frederic; Rothman, James E.
Abstract : Munc13‐1 is a large banana‐shaped soluble protein that is involved in the regulation of synaptic vesicle docking and fusion. Recent studies suggest that multiple copies of Munc13‐1 form nano‐assemblies in active zones of neurons. However, it is not known whether such clustering of Munc13‐1 is correlated with multivalent binding to synaptic vesicles or specific plasma membrane domains at docking sites in the active zone. The functional significance of putative Munc13‐1 clustering is also unknown. Here, we report that nano‐clustering is an inherent property of Munc13‐1 and is indeed required for vesicle binding to bilayers containing Munc13‐1. Purified Munc13‐1 protein reconstituted onto supported lipid bilayers assembled into clusters containing from 2 to ˜ 20 copies as revealed by a combination of quantitative TIRF microscopy and step‐wise photobleaching. Surprisingly, only clusters containing a minimum of 6 copies of Munc13‐1 were capable of efficiently capturing and retaining small unilamellar vesicles. The C‐terminal C2 C domain of Munc13‐1 is not required for Munc13‐1 clustering, but is required for efficient vesicle capture. This capture is largely due to a combination of electrostatic and hydrophobic interactions between the C2 C domain and the vesicle membrane. Abstract :